Ablation of miRNA-22 protects against obesity-induced adipocyte senescence and ameliorates metabolic disorders in middle-aged mice. (March 2023) - Lino, Caroline A.; de Oliveira-Silva, Tábatha; Lunardon, Guilherme; Balbino-Silva, Camila; Lima, Vanessa M.; Huang, Zhan-Peng; Donato Jr, Jose; Takano, Ana Paula C.; Barreto-Chaves, Maria Luiza; Wang, Da-Zhi; Diniz, Gabriela P.
Abstract: High-fat diet (HFD) promotes obesity-related metabolic complications by activating cellular senescence in white adipose tissue (WAT). Growing evidence supports the importance of microRNA-22 (miR-22) in metabolic disorders and cellular senescence. Recently, we showed that miR-22 deletion attenuates obesity-related metabolic abnormalities. However, whether miR-22 mediates HFD-induced cellular senescence of WAT remains unknown. Here, we uncovered that obese mice displayed increased pri-miR-22 levels and cellular senescence in WAT. However, miR-22 ablation protected mice against HFD-induced WAT senescence. In addition, in vitro studies showed that miR-22 deletion prevented preadipocyte senescence in response to Doxorubicin (Doxo). Loss-of-function studies in vitro and in vivo revealed that miR-22 increases H2ax mRNA and γH2ax levels in preadipocytes and WAT without inducing DNA damage. Intriguingly, miR-22 ablation prevented HFD-induced increase in γH2ax levels and DNA damage in WAT. Similarly, miR-22 deletion prevented Doxo-induced increase in γH2ax levels in preadipocytes. Adipose miR-22 levels were enhanced in middle-aged mice fed a HFD than those found in young mice. Furthermore, miR-22 deletion attenuated fat mass gain and glucose imbalance induced by HFD in middle-aged mice. Overall, our findings indicate that miR-22 is a key regulator of obesity-induced WAT senescence and metabolic disorders in middle-aged mice. Highlights: The mechanisms involved in obesity-induced white adipose tissue senescence remain not fully understood. Deletion of miR-22 prevented high-fat diet-induced white adipose tissue, senescence and DNA damage. Ablation of miR-22 prevented Doxorubicin-induced preadipocyte senescence in vitro. Deletion of miR-22 attenuated high-fat diet-induced metabolic disorders in middle-aged mice. miR-22 is a key regulator of obesity-induced white adipose tissue senescence and metabolic disorders in middle-aged mice.